O stateczności sprężystej układów niezachowawczych - OLSZOWSKI, Bogdan (Engineering Transactions, 1966)
Elastic stability of non-conservative systemsThe phenomenon of the static and dynamic of loss stability is discussed for two non-conservative mechanical systems with two degrees of freedom, These systems enable simplified description of the buckling of an axially compressed bar clamped at one end and the loss of stability of plane bending of a cantilever beam subjected to bending in the plane of greater rigidity. These phenomena are analysed, assuming that the loading force is of a «follow-up» type with every one value of the coefficient of «following-up».The part devoted to problems of static stability is concerned with the relations between the critical load and the «follow-up» coefficient. Most attention is paid to problems of dynamic stability that is the influence of the value of the «follow-up» coefficient on the location and the width of the principal regions of parametric resonance of the first and second kind. The analysis is done by means of E. Mettler's method. The conclusions concern questions of occurrence of two types of regions of the second kind (combination resonance for the sum and the difference of natural frequencies).